Synthesis and investigation of dielectric properties of a hydrogen-bonded chalcone aniline monomer and its polymer - Cogalmis, Fatma Tuba; Korkmaz, Burak; Ozerol, Esma Ahlatcioglu; Sutay, Berkay; Senkal, Bahire Filiz; Canli, Nimet Yilmaz; Gursel, Yesim (ELSEVIER, 2026)
A tertiary amine-substituted chalcone-based monomer was synthesized via a Claisen-Schmidt reaction between 3-aminoacetophenone and 4-(dimethylamino) benzaldehyde, using KOH as a base catalyst and ethanol as the solvent under ambient conditions for 24 h. The chalcone-modified aniline monomer was subsequently polymerized oxidatively using ammonium persulfate as an initiator and HBr as a doping agent in an aqueous medium for 24 h at room temperature. Additionally, a hydrogen-bonded liquid crystalline (LC) compound, 11-(4-cya-nobiphenyl-4(-oxy)undekan-1-ol (LC11), was synthesized as per the literature and employed as an H-bond donor mesogen. Both the tertiary amine-substituted chalcone monomer (Ch-ANI) and its polymer (Ch-PANI) served as hydrogen bond acceptors. The liquid crystalline behavior of the materials was investigated using DSC (Differential Scanning Calorimetry), dielectric and AC conductivity measurements, spectroscopic methods, and POM (Polarized Optical Microscopy). To elucidate the hydrogen bonding mechanism between LC11 and the synthesized materials, computational methods were employed.
Keywords: Polyaniline; Chalcone; Hydrogen bonded liquid crystal; Conducting polymer; Impedance spectroscopy (IS); Computational chemistry; Chemistry